2019
DOI: 10.1136/postgradmedj-2018-136072
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of acute severe ulcerative colitis

Abstract: Acute severe ulcerative colitis is a life-threatening medical emergency, which can be associated with significant morbidity and is preventable through prompt and effective management. Corticosteroids remain the cornerstone of initial therapy, although a third of patients will not respond. Further management hinges on timely decisions with use of rescue therapy with ciclosporin or infliximab, without compromising the health or safety of the patient, or timely surgery. Although such patients need specialist care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…Synthetic glucocorticoid immunosuppressants, especially Dex, have been widely used in treating inflammatory disorders and are well known for their effects on the immune system [7,28,[48][49][50]. It has been suggested that GCs regulate a variety of different immune cell activities [51].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Synthetic glucocorticoid immunosuppressants, especially Dex, have been widely used in treating inflammatory disorders and are well known for their effects on the immune system [7,28,[48][49][50]. It has been suggested that GCs regulate a variety of different immune cell activities [51].…”
Section: Discussionmentioning
confidence: 99%
“…If treatment is ineffective or exacerbates the condition, immunosuppressive agents such as cyclosporine A or the blocking of the secretion of the pro-inflammatory cytokine TNFα with infliximab are used for emergency intravenous infusion treatment. Partial colectomy is considered if treatment is no longer effective [2,4,7,[54][55][56]. It is important to further summarize these clinical studies, and the glucocorticoid treatment of acute ulcerative colitis, especially in the development of acute ulcerative colitis, is often ineffective or even detrimental.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the disease progresses, the beneficial effects of BNP and NT-proBNP diminish, leading to water and sodium retention and adversely affecting the heart. Therefore, the increased levels of BNP and NT-proBNP can reflect the severity of left ventricular dysfunction, which increases as the disease progresses [38]. The decision tree algorithm is a machine learning algorithm.…”
Section: Introductionmentioning
confidence: 99%